PENDAMPINGAN PENYUSUNAN JADWAL SALAT BERBASIS ILMU FALAK DI DAYAH SALAFIYAH RAUDHATUL MA’ARIF COT TRUENG ACEH UTARA - Ismail Ismail; Nazaruddin Nazaruddin; Hasna Tuddar Putri (LPPM Universitas Abdurrab, 2026)
This community service initiative is driven by the urgent need for independence in determining prayer times at Dayah Salafiyah Raudhatul Ma’arif Cot Trueng, North Aceh, which has implemented the Muadalah curriculum. Although falak (Islamic astronomy) is a mandatory subject, the practical ability of the teachers to perform hisab (mathematical calculations) and compile accurate local prayer schedules based on specific geographical coordinates remains highly limited. This activity aims to provide intensive assistance to 25 teachers to equip them with the technical competence required to calculate the start of prayer times and independently compile precise schedules. The implementation method employs the Participatory Action Research (PAR) approach, emphasizing the active participation of partners through stages of problem mapping, training on prayer time calculation algorithms, schedule preparation workshops, and verification of calculation results. Based on the outcomes, there was a significant improvement in the partners' skills, where the teachers successfully mastered contemporary hisab methods and produced local prayer schedules validated for use as a worship guide within the dayah and the surrounding community. This achievement serves as a solution to the dayah’s dependency on external schedules that may not align with the specific coordinates of the location. As a recommendation, it is suggested that these compiled schedules be widely socialized, followed by periodic evaluations and the development of further training on hilal (crescent moon) observation to complement the practical application of falak science in the pesantren.